PGRP-S promotes hepatocellular carcinoma progression via MAPK/ERK pathway by interaction with TTC1 - Huifang Zhu; Shuang Feng; Sizhen Lv; Di Zhao; Xuanhe Chang; Shangqian Fan; Xia Wang; Xinlai Qian (Scientific Reports)
Abstract Abnormal expression of PGRP-S plays an important role in the development and progression of hepatocellular carcinoma (HCC), although the mechanism has remained elusive. In this study, we aimed to investigate the biological function and potential mechanism of PGRP-S in HCC. We found that PGRP-S was upregulated in HCC tissues compared to adjacent tissues. The increased expression of PGRP-S correlated with the differentiation and lymph node metastasis of HCC. PGRP-S obviously promoted HCC cell proliferation, migration and invasion in vitro. In vivo nude mouse models showed that PGRP-S enhanced tumor growth and pulmonary metastasis. Mechanistically, PGRP-S interacted with TTC1 and activated MAPK/ERK pathway, leading to HCC cell proliferation, migration and invasion. Therfore, our conclusion is PGRP-S promotes HCC cell proliferation, migration and invasion by activating MAPK/ERK pathway, which provides a new potential strategy for HCC treatment by targeting PGRP-S-TTC1 axis.